EVALUATION OF THE ECONOMIC POTENTIAL OF COASTAL TOURISM STRATEGIC AREA OF ANYER TOURISM – CINANGKA - Kenedi, Kenedi; Irwan Sukmawan; April Laksana (SEAN Institute, 2022)
The development of tourism that is not optimal is one of the obstacles to the undevelopment of the tourism industry both in Banten Province and in Serang Regency. Serang Regency is one of the districts with considerable tourism potential to be developed and maintained. To encourage the growth of the tourism industry in Banten Province, the local government has issued Banten Provincial Bylaw No. 6 of 2019 concerning the Banten Province Tourism Development Master Plan for 2018-2025, where in the bylaw, one of the strategic development areas is the Anyer – Cinangka strategic tourism area. In the strategic area of Anyer tourism – Cinangka which is the leading tourism sector is beach tourism where there are four main beaches: Anyer Beach, Tanjung Tum Beach, Bojong Beach and Sambolo Beach. To support the bylaw, it is necessary to take several strategic steps, one of which is to see the potential of beach tourism in the area in an integrated or comprehensive manner.The purpose of this study is to evaluate the beach tourism potential of the Strategic Tourism Area of Anyer – Cinangka which includes: Anyer Beach, Tanjung Tum Beach, Bojong Beach and Sambolo Beach. The method used in this study is the Explanatory Survey Method, with data collection techniques including observations, questionnaires, interviews, documentation and literature studies. The primary data were then processed using the Integrated Beach Value Index (IBVI) method. The results of the IBVI calculation concluded that Anyer Beach – Marbella has the highest IBVI value with a moderate classification and the lowest is Bojong-Lighthouse Beach also with a moderate classification. These results can be used for comparison on each beach attraction and further research development.